Exploring A Preliminary Conceptual Framework for Integrating Sharia Compliance into Public-Private Partnership (PPP) in Indonesia (International Journal of Built Environment and Sustainability, 2025)
Public-Private Partnership (PPP) is a collaborative mechanism between the government and the private sector for delivering public infrastructure over the long term. In Indonesia, PPP plays a critical role in addressing the infrastructure investment gap, which is estimated at IDR 6,445 trillion for the 2020–2024 period. In response, there is growing interest in Sharia-compliant PPP schemes to attract investment from Sharia-conscious stakeholders. This study proposes a preliminary conceptual framework for integrating Sharia compliance into PPP in Indonesia. A two-step approach is employed: (1) a document review of Indonesian PPP regulations to establish a foundational understanding of the PPP stages and a co-occurrence analysis to identify key intersections between Sharia principles across the PPP stages. This approach helps identify key topics essential for developing the preliminary conceptual framework. The findings indicate that existing studies do not explicitly address the integration of Sharia compliance across all PPP stages. However, Sharia-compliant financing is frequently discussed in the transaction stage, while certain principles could be preliminarily integrated into the planning, preparation, and management stages. These findings form the basis for integrating Sharia compliance into PPP in Indonesia, which could serve as a foundation for further research on Sharia-based PPP policies and practice implementation in the country. In addition to proposing a preliminary conceptual framework, the study underscores the need for empirical testing and validation. Expert opinions from Sharia scholars and infrastructure specialists are crucial for refining the framework and ensuring its broader applicability across various infrastructure sectors.
Keywords: Compliance; Conceptual; Infrastructure; PPP; Sharia